The Problem of Morals in the Philosophy of Enlightenment - Kuginienė, Lolita (Problemos, 1987)
The philosophy of the modem times was infected with the idea of Enlightenment. An attempt was made here to solve practical problems by theoretical means. This intention was especially explicit in the theory of ethics: the problem of moral perfection was viewed here as the problem of knowledge. The article discloses the methodological deficiencies of the theoretical stand of Enlightenment.